Association of Admission CRP Level with Short Term Outcome in Patients with Acute Ischemic Stroke - Masud, Mahadi; Al Amin, Mohammad; Hossain, Abul; Morshed, S M Munowar; Partha Pratim Karmaker,; Islam, M M Shahin Ul; Sharifunnesa,; Rahman, ATM Ataur (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Acute ischemic stroke is very common in Bangladesh and one of the most common causes of physical disability and death. This study was performed to determine the prognostic value of CRP measured in the very early phase of ischemic stroke for short term functional outcome of patients with acute ischemic stroke. This observational study was carried out in the departments of Medicine and Neurology of Faridpur Medical College Hospital, Faridpur from July 2012 to December 2012. Total 100 patients of acute ischemic stroke were recruited in this study. Blood sample was collected for CRP level during the time of admission. In this study 26% of patients were in low CRP group (CRP <3 mg/L), 34% of patients were in medium CRP group (CRP 3-9.9 mg/L), 40% of patients were in high CRP group (CRP ≥10 mg/L). According to modified Rankin Scale (mRS) scoring system the high CRP group having a 44% risk for a poor outcome (mRS ≥3 ) vs 27% for the low CRP group ( p = 0.01). According to Barthel Index (BI) scoring system the high CRP group having a 45% risk for a poor outcome (BI <95) vs. 25% for the low CRP group (p = 0.002). Z test of proportion revealed significant association between high CRP level and poor short-term outcome of patients with acute ischemic stroke. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(1):12-15